Financial ratio and firm value: the role of firm size - Trisnawati, Anggi; Ummah, Ismatul; Parlina, Nurhana Dhea (Manajemen dan Bisnis, 2024)
This study aims to ascertain the impact of capital structure, liquidity, and profitability on firm value, with firm size serving as a moderating variable. The study population is comprised of healthcare companies that are listed on the Indonesia Stock Exchange during the period between 2020 to 2022. The research design employed in this study was that of causal research. The sampling technique employed was that of purposive sampling. This method resulted in the acquisition of 14 companies meeting the specified criteria from a total of 19 companies observed over a three-year period. The total sample size was 42 samples. The statistical analysis employed in this research is multiple linear regression, coupled with moderated regression analysis (MRA). The results show that profitability affects firm value, while capital structure and liquidity have no effect on firm value. Firm size also cannot moderate capital structure, liquidity and profitability on firm value. The implication is that companies can increase their value by focusing on increasing profitability. This can be achieved through good financial management, efficient cash flow management, and maintaining healthy debt levels.